2017
DOI: 10.1007/s10897-017-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Counselor in the Pediatric Arrhythmia Clinic: Review and Assessment of Services

Abstract: There are minimal data on the impact of genetic counselors in subspecialty clinics, including the pediatric arrhythmia clinic. This study aimed to describe the clinical encounters of a genetic counselor integrated into a pediatric arrhythmia clinic. In the 20 months between July 2015 and February 2017, a total of 1914 scheduled patients were screened for indications relevant for assessment by a genetic counselor. Of these, the genetic counselor completed 276 patient encounters, seeing 14.4% of all patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Mainstreaming is common in oncology settings and has been shown to reduce wait times and decrease costs, 98,[137][138][139] while embedding a GC in an oncology or cardiology clinic increased the number of patients seen and decreased wait times and appointment length. 92,[162][163][164] Having a GC embedded in a cardiology clinic led to better identification and triage of patients for genetic counseling and also led to an increased referral rate for patients with syndromic features for a complete genetics consultation. 163 Additional studies reported on quality improvement, tasksharing between different provider types, or information technology innovations such as automation of processes and online administrative tools.…”
Section: Opportunities To Increase Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mainstreaming is common in oncology settings and has been shown to reduce wait times and decrease costs, 98,[137][138][139] while embedding a GC in an oncology or cardiology clinic increased the number of patients seen and decreased wait times and appointment length. 92,[162][163][164] Having a GC embedded in a cardiology clinic led to better identification and triage of patients for genetic counseling and also led to an increased referral rate for patients with syndromic features for a complete genetics consultation. 163 Additional studies reported on quality improvement, tasksharing between different provider types, or information technology innovations such as automation of processes and online administrative tools.…”
Section: Opportunities To Increase Capacitymentioning
confidence: 99%
“…92,[162][163][164] Having a GC embedded in a cardiology clinic led to better identification and triage of patients for genetic counseling and also led to an increased referral rate for patients with syndromic features for a complete genetics consultation. 163 Additional studies reported on quality improvement, tasksharing between different provider types, or information technology innovations such as automation of processes and online administrative tools. Some studies streamlined workflow processes or implemented a technical or automated element and then measured impact on capacity by assessing the time saved or impact on patient throughput.…”
Section: Opportunities To Increase Capacitymentioning
confidence: 99%
“…Some types of arrhythmia, such as ventricular flutter and fibrillation, grade III atrioventricular block and long-QT syndrome, are life-threatening. Over previous decades, molecular genetics research has established a link between a number of inherited, lethal cardiac arrhythmias and disease-causing variants in genes encoding ion channels or other membrane components in adults (4)(5)(6)(7). Some studies have reported that neonatal arrhythmias, such as long-QT syndrome, are related to genetic abnormalities (3,6), but the incidence of genetic abnormalities has not been reported for newborns with arrhythmia.…”
Section: Introductionmentioning
confidence: 99%
“…They interpret genetic information, provide education and counseling, coordinate test logistics, and evaluate genetic test results. Cardiovascular genetic counselors are especially adept at evaluating variants of uncertain significance (Reuter, Grove, Orland, Spoonamore, & Caleshu, 2018) and at identifying eligible family members for additional family genetic screening (Helm et al., 2018).…”
Section: Introductionmentioning
confidence: 99%